Is conduction system pacing more effective than right ventricular pacing in reducing atrial high-rate episodes in patients with heart failure and preserved ejection fraction? - Chen, Ying; Ma, Zhu-Lin; Liu, Fei; Wang, Nan; Ma, Yue-Yang; Guan, Zi-An; Zhe, Zhuang-Chuan; Xia, Yun-Long; Dong, Ying-Xue (Frontiers in Physiology, 2024)
BackgroundThe relationship between conduction system pacing (CSP) and the incidence of atrial fibrillation (AF) in patients with heart failure and preserved ejection fraction (HFpEF) remains uncertain. This study aims to investigate the occurrence of atrial high-rate episodes (AHREs) following CSP in patients with HFpEF, in comparison to right ventricular pacing (RVP).MethodsPatients with HFpEF who received dual-chamber pacemakers for atrioventricular block were retrospectively enrolled from January 2018 to January 2023. Both new-onset and progressive AHREs were recorded, along with other clinical data, including cardiac performance and lead outcomes.ResultsA total of 498 patients were enrolled, comprising 387 patients with RVP and 111 patients with CSP, with a follow-up duration of 44.42 ± 10.41 months. In patients without a prior history of AF, CSP was associated with a significantly lower incidence of new-onset AHREs when the percentage of ventricular pacing was ≥20% (9.52% vs. 29.70%, P = 0.001). After adjusting for confounding factors, CSP exhibited a lower hazard ratio for new-onset AHREs compared to RVP (HR 0.336; [95% CI: 0.142–0.795]; P = 0.013), alongside left atrial diameter (LAD) (HR 1.109; [95% CI: 1.048–1.173]; P < 0.001). In patients with a history of AF, the progression of AHREs in CSP and RVP did not differ significantly (32.35% vs. 34.75%, P = 0.791). Cardiac performance metrics, including left ventricular end-diastolic diameter (LVEDD) (49.09 ± 4.28 mm vs. 48.08 ± 4.72 mm; P = 0.015), LAD (40.68 ± 5.49 mm vs. 39.47 ± 5.24 mm; P = 0.001), and NYHA class (2.31 ± 0.46 vs. 1.59 ± 0.73; P < 0.001), improved obviously following CSP, while LVEDD (48.37 ± 4.57 mm vs. 49.30 ± 5.32 mm; P < 0.001), LAD (39.77 ± 4.58 mm vs. 40.83 ± 4.80 mm; P < 0.001), NYHA class (2.24 ± 0.43 vs. 2.35 ± 0.83; P = 0.018), and left ventricular ejection fraction (LVEF) (57.41 ± 2.42 vs. 54.24 ± 6.65; P < 0.001) deteriorated after RVP.ConclusionOur findings suggest that CSP may be associated with improvements in cardiac performance and a reduction in new-onset AHREs compared to RVP in patients with HFpEF. However, prospective randomized trials are anticipated to confirm these potential benefits.